Види атак на IoT Smart House - Куля, Ю. Е.; Квашенко, В. Р. (ХНУРЕ, 2024)
Internet of Things is a rapidly evolving technology in which interconnected computing devices, sensors share data to detect and act accordingly to situation and deliver smart services like temperature monitoring, automatic light con-trol, smart locks, smoke detection, etc. But it also opens the door to new set of security and privacy issues, such as personal and private data of users. In this paper, we discuss multilayer structure of IoT, and what security challenges faces each layer.
Keywords: IoT Smart House; класифікація атак